2018
DOI: 10.1159/000496805
|View full text |Cite
|
Sign up to set email alerts
|

Is Head Computerized Tomography Indicated for the Workup of Headache in Patients with Intact Neurological Examination

Abstract: Introduction: The use of neuroimaging as part of the initial workup in the emergency department (ED) for patients with atraumatic headache is increasing, whereas the proportion of cases in which clinically significant intracranial pathology is detected is decreasing. In the last few decades, the exposure to medical ionized radiation from utilization of computer tomography (CT) increased dramatically, raising concern about radiation-induced cancer. Different guidelines were suggested to address the role of neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Typical "red flags" in the clarification of headaches are patient age over 50 years, immunosuppression, an abnormal neurological examination finding or additional symptoms such as fever. However, a study by Goldstein et al 2018 also showed that a normal neurological finding in patients with headaches does not rule out a secondary headache and pathological brain imaging findings (17). The care of patients with headache in the ED represents a challenging and cost-intensive task, especially in times of increasing demand by patients (18,19).…”
Section: Introductionmentioning
confidence: 99%
“…Typical "red flags" in the clarification of headaches are patient age over 50 years, immunosuppression, an abnormal neurological examination finding or additional symptoms such as fever. However, a study by Goldstein et al 2018 also showed that a normal neurological finding in patients with headaches does not rule out a secondary headache and pathological brain imaging findings (17). The care of patients with headache in the ED represents a challenging and cost-intensive task, especially in times of increasing demand by patients (18,19).…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19] In the last two decades, overall imaging utilization, regardless of indication, has been on the rise in the United States, 20 including both the adult and pediatric ED settings [21][22][23][24] with up to 30.0% of currently performed medical imaging of dubious clinical necessity. 23,25,26 The scope and focus of prior studies investigating the use of imaging in headache were limited to outpatient settings, 1,27 ED settings before 2007, 23,28 single-institution cohorts, 6 short (1 year) study periods, 6,29 and single imaging modality, 29 or were based on patient-generated data obtained through household surveys. 22 Longitudinal population-level patterns of imaging utilization for headache in US EDs in the last decade remain unknown.…”
Section: Introductionmentioning
confidence: 99%